Nhoroondo muridzi wayo: the changing nature of archaeological research and heritage management at Great Zimbabwe - Tevera, Genius (Department of Archaeology, 2025)
Archaeology is an important avenue that people use to understand their past, as well as to create and maintain their identities. Unfortunately, the practice of archaeology in Africa is marred by western ideologies, which do not give much consideration to the needs of local communities. This thesis explores the changing nature of archaeological research at Great Zimbabwe World Heritage Site and its interface with surrounding communities, using a framework provided by de-colonial thinking. De-colonial discourses urge the discipline to overcome its colonial inheritance in favour of a more inclusive approach that takes cognisance of the fact that archaeology affects people's lives not only in the physical aspects, but also strongly in its ideological effect. The world-famous nature of Great Zimbabwe makes it a profitable venue for exploring whether knowledge production dynamics and power relations have remained colonial or not. More importantly, it is a question as to whether calls to incorporate local communities into building interpretation narratives have resulted in meaningful power sharing and are communities being given space to tell their own nhoroondo (narratives). To address these and other questions, a mixed research methodology combining both qualitative and quantitative approaches was used to explore the relationship between local and indigenous communities around Great Zimbabwe and various dimensions of archaeology and heritage management. A desktop analysis of archaeological research trends at the site was carried out. Questionnaires and interviews were used to determine community perceptions and attitudes towards archaeologicalpractices. The study concludes that most communities associated with the site have their own narratives and are fighting for space to be heard. They strongly feel that dominant narratives and interpretations at the site are not in sync with local narratives and beliefs. Informed by local ways of doing and thinking, they see themselves as better placed to tell narrate their histories. The research argues that ‘nhoroondo muridzi wayo' (a narrative is better told by its owner) and motivates for an inclusionary approach, which recognises indigenous epistemologies and perspectives in constructing and deconstructing our knowledge of Great Zimbabwe.